Improving cost performance in design-bid-build road projects by mapping the reasons for cost overruns into the project phases. - Calahorra-Jimenez, Maria; Alarcon, Luis Fernando; Torres-Machi , Cristina; Chamorro, Alondra; Molenaar, Keith (Revista de la Construcción. Journal of Construction, 2020)
Alternative project delivery methods such as design-build (DB) have shown to be better for controlling cost growth comparing with the traditional Design-Bid-Build (DBB) method. The purpose of this research is to identify the main reasons for cost overruns in the design, the procurement and the construction phases of DBB road projects as a point of departure to find specific elements of DB project delivery that might help to minimize these reasons. To identify these reasons, an exploratory content analysis was performed based on the study of 41 interviews conducted with professionals involved in road project management in Chile. Literature review and document analysis of DB were used to analyze the identified reasons under the framework of the DB practice in the United States. The results showed that four elements based on the DB approach might be used to minimize cost overruns in DBB projects: (1) In the design phase, road administrators should consider the early integration of the constructor’s expertise. In the procurement phase, they should establish (2) instances for effective information exchange and (3) a goal-oriented selection process. Overall, road administrators should consider (4) establishing a one-point of high-level accountability for the design, the procurement, and the construction phases. This study will serve DBB road administrators to start the transition from DBB to more collaborative approaches that will help to minimizer cost overruns and therefore, to improve the project cost performance.